Advances in basic research of traditional Chinese medicine herbal formulae in the treatment of non-small cell lung cancer - Linwei Lu; Jingcheng Dong; Weiyi Gong (World Scientific Publishing, 2021)
Today, there is an increasing rate of morbidity and mortality in lung cancer worldwide. In China, lung cancer is also the leading cause of cancer-related death in China. The distinctive herbal therapy from traditional Chinese medicine (TCM) has shown good efficacy in treating lung cancer principally by inhibiting tumor growth or improving the anti-tumor immune response according to considerable experimental studies, which also justifies the concept of dispelling pathogenic qi and strengthening healthy qi in TCM.